Suicide in Healthcare Workers: Determinants, Challenges, and the Impact of COVID-19 - Awan, Sana; Diwan, Mufaddal Najmuddin; Aamir, Alifiya; Allahuddin, Zoha; Irfan, Muhammad; Carano, Alessandro; Vellante, Federica; Ventriglio, Antonio; Fornaro, Michele; Valchera, Alessandro; Pettorruso, Mauro; Martinotti, Giovanni; et al. (Frontiers in Psychiatry, 2022)
The Coronavirus disease-19 (COVID-19), which first appeared in Wuhan, China, and was later declared a pandemic, has caused significant morbidity and mortality worldwide. Numerous efforts have been made worldwide to understand the disease's physical manifestation. However, less emphasis has been placed on the pandemic's mental health challenges for healthcare workers (HCWs) who played a critical role in fighting the disease. Existing literature shows the detrimental psychological impact and increased incidence of depression and anxiety among HCWs. It is expected that the mental health crisis will become a serious issue affecting HCWs, with long-term negative consequences following COVID. Physicians and nurses already represent the highest risk groups of suicide among the general population, and suicide can be regarded as an occupational hazard in the healthcare industry. Increased workload, burnout and fatigue, multifaceted challenges women HCWs, and increased substance abuse are contributing factors to suicide ideation. In this article, we identify the risk factors of suicide among HCWs, discuss mental health challenges exacerbated by the pandemic and its impact on suicide ideation.